Military-related risk factors in female veterans and risk of dementia. (15th January 2019) - Yaffe, Kristine; Lwi, Sandy J.; Hoang, Tina D.; Xia, Feng; Barnes, Deborah E.; Maguen, Shira; Peltz, Carrie B.
Abstract : Objective: To determine whether diagnoses of traumatic brain injury (TBI), posttraumatic stress disorder (PTSD), and depression, alone or in combination, increase dementia risk among older female veterans. Methods: This cohort study included data from 109, 140 female veterans ≥55 years of age receiving care from Veterans Health Administration medical centers in the United States between October 2004 and September 2015 with at least 1 follow-up visit. TBI, PTSD, depression, and medical conditions at study baseline and incident dementia were determined according to ICD-9-CM codes. Fine-Gray proportional hazards models were used to determine the association between military-related risk factors and dementia diagnosis, accounting for the competing risk of death. Results: During follow-up (mean 4.0 years, SD 2.3), 4% of female veterans (n = 4, 125) developed dementia. After adjustment for demographics and medical conditions, women with TBI, PTSD, and depression had a significant increase in risk of developing dementia compared to women without these diagnoses (TBI-adjusted subdistribution hazard ratio [adjusted sHR] 1.49, 95% confidence interval [CI] 1.01–2.20; PTSD adjusted sHR 1.78, 95% CI 1.34–2.36; and depression-adjusted sHR 1.67, 95% CI 1.55–1.80), while women with >1 diagnosis had the highest risk for dementia (adjusted sHR 2.15, 95% CI 1.84–2.51). Conclusions: We found that women with military-related risk factors had an ≈50% to 80% increase in developing dementia relative to women without these diagnoses, while female veterans with multiple risk factors had a >2-fold risk of developing dementia. These findings highlight the need for increased screening of TBI, PTSD, and depression in older women, especially female veterans.